Los saberes docentes en la internalización y en el uso del currículum en el nivel preescolar - Martínez Barradas, Rosa Lilian (2022)
Some reflections are presented in relation to the influence that professional training has had the management of the curricular knowledge of two Mexican educators. It is intended to understand the link between teaching knowledge in the face of the internalization and the use of the curriculum in the face of the emergency determined by the pandemic. Qualitative and hermeneutic research, uses in depth interviews, narrative biographical accounts and observation records of teaching intervention as information collection techniques. The main results indicate that there is a permanent tension between professional knowledge, experiential knowledge and institutional demands that sometimes obey a technical rationality form the formality of the curriculum. Such tension, evidences that teachers are not simple applicators of the curriculum, but are constituting knowledge that is built from from one’s own subjectivities